The structure of fantasy - Hall, Eric (1979)
The focus of this study is on guided fantasy; a technique which is increasingly used in educational and psychotherapeutic situations. The potential coherence of guided fantasy is examined by establishing the degree to which the elements of various guided fantasy experiences are perceived as being similar.